Titanium-supported W-containing PEO layers enriched with Mn or Zn in oxidative desulfurization and the zwitterionic liquid effect - Bryzhin, A. A.; Tarkhanova, I. G.; Gantman, Mikhail; Rudnev, V. S.; Vasilyeva, M. S.; Lukiyanchuk, I. V. (Surface & Coatings Technology, 2020)
Titanium-supported oxide layers of W, W + Zn and W + Mn, formed by plasma electrolytic oxidation, were established to catalyze the peroxide oxidation of thiophene. The most active compositions based on Zn-W-containing PEO layers were also tested in the oxidation of a number of organosulfur compounds and diesel fuel desulfurization. Preliminary covering the samples by zwitterionic liquid (ZIL) made it possible to achieve residual sulfur content as low as 6 ppm. The change in the morphology and composition of samples with and without ZIL was studied during catalytic tests. It was found that ZIL reduces the etching of the sample surfaces when interacting with the reaction medium.
CRIS-Team Scopus Importer:2020-04-28
Keywords: MnWO; Oxidative desulfurization; Plasma electrolytic oxidation; Surface behavior; Titanium-supported catalysts; Zwitterionic liquid effect